Existence and Positivity of Solutions for a Second-Order Boundary Value Problem with Integral Condition - Assia Guezane-Lakoud; Hamidane Nacira; Khaldi Rabah (International Journal of Differential Equations)
This work is devoted to the study of uniqueness and existence of positive solutions for a second-order boundary value problem with integral condition. The arguments are based on Banach contraction principle, Leray Schauder nonlinear alternative, and Guo-Krasnosel’skii fixed point theorem in cone. Two examples are also given to illustrate the main results.